Shaping STEM Pathways: The Role of Language Education Policies in Guiding Future Engineers in the USA (International Journal of Scientific Research and Management (IJSRM), 2022)
The influence of language education policies on students’ career decisions, particularly within STEM disciplines, has garnered considerable focus in recent years. In the U.S., such policies play a pivotal role in shaping the academic journeys of students, particularly those from multilingual backgrounds, as they navigate the path toward engineering and other STEM professions. This article delves into how language education policies affect STEM career trajectories, emphasizing how evolving policies are motivating a new generation of engineers in the U.S. By conducting an in-depth examination of current educational policies, language instruction, and culturally responsive social-emotional learning (SEL), the study illustrates the critical role of integrating language education with STEM curricula. The results highlight the essential need to support underrepresented communities and demonstrate the benefits that result from effective policy frameworks. By analyzing research trends, identifying policy shortcomings, and addressing challenges faced by multilingual learners, this article sheds light on the future landscape of STEM education in the U.S. Furthermore, it discusses the implications for policymakers, educators, and scholars, offering strategic recommendations to cultivate a more inclusive and equitable learning environment that drives student success in STEM fields.